2012
DOI: 10.1302/0301-620x.94b1.27514
|View full text |Cite
|
Sign up to set email alerts
|

Upsizing the femoral component increases patellofemoral contact force in total knee replacement

Abstract: In posterior stabilised total knee replacement (TKR) a larger femoral component is sometimes selected to manage the increased flexion gap caused by resection of the posterior cruciate ligament. However, concerns remain regarding the adverse effect of the increased anteroposterior dimensions of the femoral component on the patellofemoral (PF) joint. Meanwhile, the gender-specific femoral component has a narrower and thinner anterior flange and is expected to reduce the PF contact force. PF contact forces were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 34 publications
2
67
2
1
Order By: Relevance
“…Studies have shown that using a larger femoral component could increase the patellofemoral contact force in TKA and possibly restrict knee range of motion including introducing a flexion contracture [27,28]. However, the results of this study do not show any correlation between implant size and flexion contracture 12 months postoperatively.…”
Section: Discussioncontrasting
confidence: 76%
“…Studies have shown that using a larger femoral component could increase the patellofemoral contact force in TKA and possibly restrict knee range of motion including introducing a flexion contracture [27,28]. However, the results of this study do not show any correlation between implant size and flexion contracture 12 months postoperatively.…”
Section: Discussioncontrasting
confidence: 76%
“…The PFJ loading is influenced both by changes in the joint line height and by selecting a femoral component that is too large [39,53] . Tibia-femoral instability, due to inappropriate placement or other causes, leads to increased pressure on the PFJ, especially in flexion [54] .…”
Section: Regeneration Of Nervesmentioning
confidence: 99%
“…It has been demonstrated that women, on average, have smaller distal femurs as well as clinically significant variation in distal femur morphology compared to their male counterparts. One morphological variation in particular is a much larger aspect ratio (anterior/posterior to medial/lateral measurement) which places this patient population at a higher risk for medial/lateral femoral component overhang [35,[37][38][39][40][41] . Different body morphologic types have a significant correlation with distal femoral morphology.…”
Section: Patellofemoral Overstuffingmentioning
confidence: 99%
“…Previous studies have considered various modifications of the anterior flange of the femoral component in order to reduce anterior impingement and pain following TKA. A femoral component with a wider and thicker anterior flange can lead to stuffing of the patello-femoral joint leading to increased patellar ligament tension and thus increased patellofemoral contact forces [35] . This will eventually cause accelerated polyethylene wear and an overall higher risk of patellar complications [35] .…”
Section: Anterior Impingement (Figure 1)mentioning
confidence: 99%